2021
DOI: 10.3390/vetsci8020029
|View full text |Cite
|
Sign up to set email alerts
|

Identification by MALDI-TOF MS and Antibiotic Resistance of Riemerella anatipestifer, Isolated from a Clinical Case in Commercial Broiler Chickens

Abstract: The Gram-negative bacterium Riemerella anatipestifer (RA) is known to cause clinical disease with severe economic impacts primarily in ducks and less frequently in geese and turkeys. RA was isolated and identified in broiler chickens, from a clinical case in a commercial broiler farm located in the southwest mainland of Greece. The morbidity and the mortality in the broiler house were estimated at 10% and 5% respectively. The observed clinical signs appeared at the age of 30 to 42 days with respiratory distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Our studies described RA occurrence in different commercial poultry species in Poland. Infections with RA in commercial geese flocks were also reported in Austria [ 4 ] and Hungary [ 28 ], Tzora et al [ 29 ] identified an RA infection on a broiler chicken farm located in the southwestern mainland of Greece, and the isolation of RA was also confirmed from a turkey farm located in Croatia [ 30 ]. Although Poland is one of the leaders in poultry production in Europe, there is not enough data about the occurrence of RA infections in the country.…”
Section: Discussionmentioning
confidence: 92%
“…Our studies described RA occurrence in different commercial poultry species in Poland. Infections with RA in commercial geese flocks were also reported in Austria [ 4 ] and Hungary [ 28 ], Tzora et al [ 29 ] identified an RA infection on a broiler chicken farm located in the southwestern mainland of Greece, and the isolation of RA was also confirmed from a turkey farm located in Croatia [ 30 ]. Although Poland is one of the leaders in poultry production in Europe, there is not enough data about the occurrence of RA infections in the country.…”
Section: Discussionmentioning
confidence: 92%
“…The identification of Staphylococcus spp. isolates at species level was carried out by MALDI-TOF MS, which has previously been used by our research group to identify clinical isolates [ 29 ], as well as by others to identify S. aureus and CoNS strains isolated from milk samples of goats with subclinical mastitis [ 12 , 19 , 40 ]. This easy-to-use, high-throughput and cost-effective technology provides rapid and accurate bacterial identification at genus and species level, rendering it a diagnostic tool with increasing popularity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated bacteria were identified by MALDI-TOF MS as described previously [ 27 , 28 , 29 ]. The direct colony method, which involves the application of bacterial colonies from growth plates directly onto the steel plate before testing by MALDI-TOF MS, was used.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, clinical prevention and control of R. anatipestifer infection in ducks are mainly dependent on antibiotics and the most commonly used antibiotics are amides, cephalosporin, and aminoglycoside. However, recent studies showed that the isolates of R. anatipestifer were resistant to multi-antibiotics ( Tzora et al, 2021 ). Antibiotic efflux is an important antibiotic-avoidance mechanism of bacteria, via recognizing and transporting out drugs ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%